ANALISIS PENYIMPANAN DAN PENDISTRIBUSIAN LOGISTIK OBAT (STUDI KASUS DI INSTALASI FARMASI DINAS KESEHATAN KABUPATEN KLATEN) - Anisa Trianingrum; Bambang Budi Raharjo (Jurnal Kesehatan Masyarakat, 2022)
The level of drug availability in the Klaten Regency Health Office in 2020 amounted to 83.33%, a decrease from the previous year so that it has not met the national target of 90%. The purpose of this study was to determine the process of implementing the storage and distribution of drug logistics in the Klaten Regency Pharmacy Installation based on the guidelines of the Ministry of Health on Pharmacy Management in the Regency Pharmacy Installation. This type of research is descriptive qualitative research with case study design. The implementation of drug storage and distribution logistics in the pharmacy installation of the Klaten District Health Office is not fully in accordance with the guidelines of the Ministry of Health. The conclusions in this study include inadequate drug storage space, facilities for drug storage are not in accordance with the guidelines of the Ministry of health, drug distribution is not in accordance with the order letter of the Puskesmas and drug vacancy occurs. Suggestions for pharmacy installation Klaten District Health Office is expected to complement the facilities and infrastructure and provide logistics management training.